(untitled) (Revista de Crítica Literaria Latinoamericana, 2022)
This article focuses on the poetry and other textualities of the Peruvian poet and painter José María Eguren. The consideration of his poetic gesture as a dissident one allows us to argue that Eguren creates in his work a scopic praxis that debates with the hegemonic visuality of his time. In this sense, I interpret how the Peruvian poet builds scenarios where the desire to look is focused on the tiny beings of nature in order to value them. In this way, Eguren’s gaze, anticipating environmentalist and animalistic positions, questions the pretensions of domination, extraction and erasure that sustained the dominant gaze of his time